2008
DOI: 10.1016/j.pain.2008.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Onset, prognosis and risk factors for widespread pain in schoolchildren: A prospective 4-year follow-up study

Abstract: Little is known about the epidemiology of widespread pain (WSP) in children and adolescents. This study aims to estimate the new-onset and prognosis of WSP in schoolchildren and investigate factors predicting its development. A prospective study was conducted among 1756 schoolchildren (age 10-12 years) in Southern Finland. At baseline, information was collected on WSP, regional musculoskeletal pain symptoms, depressiveness, fatigue, sleep problems, physical activity and joint hypermobility. These children were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
79
2
9

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(105 citation statements)
references
References 17 publications
15
79
2
9
Order By: Relevance
“…17 Neck/shoulder pain at 14 years of age was identified as increasing the odds for LBP, with and without impact, highlighting that for many people, LBP is comorbid with other pain areas, as previously reported. 24,33 This supports the view that LBP in these cases may be part of a clinical presentation of widespread pain rather than a local tissue disorder.…”
Section: Meaning Of the Study: Possible Explanationssupporting
confidence: 74%
“…17 Neck/shoulder pain at 14 years of age was identified as increasing the odds for LBP, with and without impact, highlighting that for many people, LBP is comorbid with other pain areas, as previously reported. 24,33 This supports the view that LBP in these cases may be part of a clinical presentation of widespread pain rather than a local tissue disorder.…”
Section: Meaning Of the Study: Possible Explanationssupporting
confidence: 74%
“…When considering only high-quality evidence, similar rates are found (high-quality findings; two studies 34,38 reported significant higher risk, one study 31 mixed, and five findings 31,[35][36][37] no higher risk). Overall, this indicates a trend toward strong evidence of no effect of poor sleep quality as a risk factor for the onset of musculoskeletal pain.…”
Section: Sleep Qualitysupporting
confidence: 62%
“…Of eight findings, two 34,37 (high quality) report a significant effect (both findings in the direction of daytime tiredness predictive of musculoskeletal pain), three 31 (high quality) report mixed effects, and three 36,39,42 (two high quality) report no significant effect indicating inconsistency, with a similar conclusion if only high-quality evidence is considered (please see Table 6 for a full description of effect sizes). Examination by body site revealed one high-quality 31 study reporting mixed evidence and one medium-quality 39 study reporting no effect for back pain onset.…”
Section: Daytime Tirednessmentioning
confidence: 97%
See 2 more Smart Citations